PENGARUH PENERAPAN E-BILLING SYSTEM, E-FILING SYSTEM DAN PENURUNAN TARIF PAJAK PENGHASILAN FINAL TERHADAP KEPATUHAN WAJIB PAJAK PELAKU UMKM DI KOTA DENPASAR - Made Christin Dwitrayani (Juara: Jurnal Riset Akuntansi, 2020)
Taxpayer Compliance is a condition when the Taxpayer understands or tries to understand all the provisions of the tax laws and regulations, fills the tax forms completely and clearly, calculates the amount of tax owed correctly, and pays the tax due on time. In essence, taxpayer compliance is influenced by the condition of the tax administration system which includes tax service and tax enforcement. The improvement of tax administration itself is expected to encourage taxpayer compliance. This study will examine the effect of the application of E-billing, e-filling, and a reduction in the final income tax rate on taxpayer compliance of micro, small and medium enterprises in Denpasar City.). The sample in this study were 100 micro, small and medium enterprises (MSMEs) registered at the West Denpasar KPP and East Denpasar KPP in 2018. The determination of the sample was using the proportionate stratified random sampling method. The analytical tool used is multiple linear regression analysis. The results showed that the variable application of E-billing has a positive effect on taxpayer compliance of micro, small and medium enterprises (MSMEs), E-filinghas a positive effect on taxpayer compliance of micro, small and medium enterprises (MSMEs) and decreases in final income tax rates had an effect positive on compliance with tax payments for micro, small and medium enterprises (MSMEs).